KAJIAN PENANGANAN BANJIR DI WILAYAH RW 24 DAN RW 28, KELURAHAN CIPAGERAN, KECAMATAN CIMAHI UTARA, KOTA CIMAHI - Shiddiq, Raden Herdian Bayu Ash; Hasan, Fuad; Roespinoedji, Roeshartono (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
The construction of residential canals in Cimahi City is one of the jobs that needs to be carried out considering that the canal capacity often exceeds the limit. This condition often causes puddles when the rainy season arrives. The occurrence of waterlogging, especially during the rainy season, in several residential areas has an impact on socio-economic aspects and the lives of local communities. Inundation occurs due to drainage channels not functioning properly. This research aims to analyze the capacity of existing channels and provide design recommendations for handling floods in the RW 24 and RW 28 areas, Cipageran Village, North Cimahi District, Cimahi City. In this research, primary data was collected, namely measuring the topography and dimensions of the existing channel. Interviews were also conducted with local residents to get an overview of the problems and modeling calibration data. This research uses modeling assistance with SWMM software. From the research results, it was found that the existing channel dimensions can still accommodate flow discharge with return periods of 2, 5, 10, 25, 50 and even 100 years. However, the condition of existing channels that are not maintained and high sedimentation causes a decrease in channel capacity, so that during the rainy season water overflows occur due to reduced channel capacity. So it is recommended to build a channel cut of approximately 180 meters to reduce the flow rate in the existing channel.